How Pre-service Teachers' Beliefs and Assumptions About Diverse Students Change through their Reflections on a Study-Buddy Program - Deborah Sardo Brown; Fanni Liu Coward (The Advocate, 2011)
Fifth-three pre-service teachers participated in a study-buddy program and wrote reflective journal entries and a field experience paper in which they analyzed their study-buddy's learning dilemmas and proposed possible solutions. The pre-service teachers' writings were then analyzed for assumptions they made about their study-buddy. The results of the study documented the nature of pre-service teachers' assumptions about the diverse students they tutored and how these assumptions changed over time. In addition, this study illustrated how reflective assignments, in conjunction with participation in a study-buddy program, can serve to facilitate change in pre-service teachers' preconceived notions about diverse students.